2022
DOI: 10.3390/jmse10081113
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Luminescent Bacteria in Deep Sea Marine Organisms from Sicilian Waters (Mediterranean Sea)

Abstract: Luminescent bacteria are a fascinating component of marine microbial communities, often related to the light emissions in deep sea marine organisms. They are mainly affiliated with specific phylogenetic groups, such as Photobacterium, Vibrio, and Photorhabdus, and are sometimes involved in symbiotic relationships. However, the luminescence of some marine organisms remains a poorly understood process, and it is not always certain whether their luminescence is attributable to associated luminescent bacteria. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…1 ), comprising 89.2% Photobacterium and 2.3% Shewanella species. Photobacterium species are luminous, halophilic, Gram-negative species that are present in the gut of deep-sea fish ( 12 ). Shewanella species are barotropic, luminous, Gram-negative species that are found in oceans ( 13 15 ).…”
Section: Announcementmentioning
confidence: 99%
“…1 ), comprising 89.2% Photobacterium and 2.3% Shewanella species. Photobacterium species are luminous, halophilic, Gram-negative species that are present in the gut of deep-sea fish ( 12 ). Shewanella species are barotropic, luminous, Gram-negative species that are found in oceans ( 13 15 ).…”
Section: Announcementmentioning
confidence: 99%
“…Interestingly, as in Sepioteuthis lessoniana, bioluminescent bacteria have been identified in a sepiolid species that is considered non-luminescent. Neorossia caroli lacks a light organ (Sanchez et al, 2021;Calogero et al, 2022); yet bioluminescent bacteria (Photobacterium kishitanii and P. leiognathi) were found in samples taken from the siphon and the mantle (Calogero et al, 2022). The relationships between the non-luminous cephalopods S. lessoniana and N. caroli and the respective bioluminescent bacteria found, in terms of light production, would then be facultative rather than obligate (Zari et al, 2020;Calogero et al, 2022).…”
Section: Sepiolidamentioning
confidence: 99%
“…Neorossia caroli lacks a light organ (Sanchez et al, 2021;Calogero et al, 2022); yet bioluminescent bacteria (Photobacterium kishitanii and P. leiognathi) were found in samples taken from the siphon and the mantle (Calogero et al, 2022). The relationships between the non-luminous cephalopods S. lessoniana and N. caroli and the respective bioluminescent bacteria found, in terms of light production, would then be facultative rather than obligate (Zari et al, 2020;Calogero et al, 2022). However, no studies have yet investigated such associations for purposes other than bioluminescence.…”
Section: Sepiolidamentioning
confidence: 99%
“…Twenty of these isolates were pigmented, and it was suggested that these pigments could help them to survive in Antarctic low temperatures and harmful levels of UV radiation. Meanwhile, in their work, Calogero et al [2] focused on luminescent bacteria isolated, for the first time, from the cephalopod Neorossia caroli and the teleost Chlorophthalmus agassizi from deep sea environment. The authors obtained twenty-four luminescent isolates and also investigated their biotechnological potential by studying the production of extracellular polymeric substances (EPSs).…”
mentioning
confidence: 99%